2013
DOI: 10.7150/ijbs.6022
|View full text |Cite
|
Sign up to set email alerts
|

Identification, mRNA Expression, and Functional Analysis of Chitin Synthase 1 Gene and Its Two Alternative Splicing Variants in Oriental Fruit Fly, Bactrocera dorsalis

Abstract: Two alternative splicing variants of chitin synthase 1 gene (BdCHS1) were cloned and characterized from the oriental fruit fly, Bactrocera dorsalis (Hendel). The cDNA of both variants (BdCHS1a and BdCHS1b) consisted of 5,552 nucleotides (nt), with an open reading frame (ORF) of 4,776 nt, encoding a protein of 1,592 amino acid residues, plus 685- and 88-nt of 5′- and 3′-noncoding regions, respectively. The alternative splicing site was located between positions 3,784-3,960 and formed a pair of mutually exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 49 publications
3
78
0
2
Order By: Relevance
“…In the present paper, we found that LdChSAa and LdChSAb were highly expressed in ectodermally-derived epidermal cells forming epidermis, trachea, foregut and hindgut, whereas LdChSB was mainly transcribed in midgut cells in L. decemlineata . Similar tissue-biased expression profiles have been documented in other insect species 24, 33, 34. Therefore, we compared the RNAi efficiency in the epidermis and in the midgut by ingestion of dsRNAs respectively targeting LdChSA and LdChSB in L. decemlineata larvae.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In the present paper, we found that LdChSAa and LdChSAb were highly expressed in ectodermally-derived epidermal cells forming epidermis, trachea, foregut and hindgut, whereas LdChSB was mainly transcribed in midgut cells in L. decemlineata . Similar tissue-biased expression profiles have been documented in other insect species 24, 33, 34. Therefore, we compared the RNAi efficiency in the epidermis and in the midgut by ingestion of dsRNAs respectively targeting LdChSA and LdChSB in L. decemlineata larvae.…”
Section: Discussionsupporting
confidence: 58%
“…In T. castaneum , ds TcChSAa disrupted larval-larval, larval-pupal, and pupal-adult ecdysis, while ds TcChSAb only influenced pupal-adult molting 2, 7. Knockdown of BdChSAa + BdChSAb or only BdChSAa in B. dorsalis had a similar result in that the larvae were trapped in old cuticles and died without completely tanning, whereas injection of ds BdChSAb into B. dorsalis third (final) instar larvae caused no visible abnormal morphological changes, and no influence on pupation 24. In L. migratoria , ds LmChSAa resulted in three different lethal phenotypes, i.e., translucent new cuticle, trouble shedding old cuticle, and stunted development, whereas ds LmChSAb only caused crumpled cuticle 17.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The final concentration of dsRNA was 1.5 lg/lL. According to the method described by Yang et al (2013) with modifications, approximately 1 lg of dsRNA was slowly injected into the antepenultimate abdominal segments of 3-day-old 3rd instar larvae with a Nanoject II Auto-Nanoliter Injector (Drummond Scientific, Broomall, PA, USA). Control larvae were injected with equivalent volumes of dsGFP.…”
Section: Double-stranded Rna Synthesis and Injectionmentioning
confidence: 99%